Soursop Leaf Water Decoction Against Decreased Uric Acid Levels in Menopause - Warsilia, Ni Nengah Susanti; Matoka, Ade Fitriyani; Hiola, Tumartony Thaib; Podungge, Yusni (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2022)
Menopausal women are 60% more likely to develop gout, this is caused by a decrease in levels of the hormone estrogen which causes uncontrolled uric acid disposal. Gout sufferers who continue to take analgesic drugs will cause side effects that are berbahaya so that nonpharmacological treatment is needed. One of the nonpharmacological treatments is the provision of soursop leaf water decoction. The purpose of this study was to find out the effect of giving soursop leaf water decoction on the decrease in uric acid levels in menopausal mothers in Limba B Village of Gorontalo City. This research method uses pre-experiments with the design of one group pre-test-post-test. With a study population of 35 people and a sample of 15 people taken using purposive sampling techniques. The results of the research analysis used the Paired Sample T-Test which showed that there was an effect of giving soursop leaf water decoction before and after being given soursop leaf water decoction. with a value of p = 0.000 (<0.05) which means H0 is rejected and Ha is accepted. Based on the results of research it can be concluded that the decoction of soursop leaf water has an effect on the decrease in uric acid levels in menopause.